Somatic and typological differentiation of first-year male and female students from the Jozef Pilsudski University of Physical Education in Warsaw" - Karol Gryko; Anna Kopiczko; Krzysztof Krawczyk; Iwona Maliszewska; Krzysztof Perkowski (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2019)
University education is a period of human life when lifestyles or person's activity are critical to the development of somatic build, while identification of the somatotype allows for corrections or recommendation of effective physical activity programmes. The main aim of this study was to assess selected features of body build and to identify somatotypes of young people at early stages of education at Jozef Pilsudski University of Physical Education in Warsaw depending on the field of study. The study examined 394 students of physical education (PE) and sport (S). Anthropometric measurements were the main research method used in the study. Physical body build (somatotype) was identified using the Heath-Carter method. The ANOVA/MANOVA analysis of variance was employed to determine the significance of differences in values of anthropometric and somatic characteristics between the groups of students. Students of physical education were characterized by a somatotype with a code of 3.08-4.6-2.62 (endomorphic mesomorph). In students of sport, the somatotype code was 3.0-4.58-2.37 (endomorphic mesomorph). Compared to S students, significantly (p < 0.05) higher values (by 10.5%) of the ectomorphy component were found in PE students. The results revealed the need for more research into the somatic build of students of physical education, taking into account the changes in their living conditions (including socio-economic environment), since graduates are expected to promote physical activity in the future. It is also necessary to carry out identical research at the end of studies in order to evaluate the effect of university curricula on the somatic build of students.